English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

g(x)=x^2-5x+2=?

if i create an analogy out of this, g is like a machine. g(x) means that you're putting x into the machine. let say if you put a banana into the machine, g(banana), all the subsequent x in the qn (g(x)=x^2-5x+2) will be replaced by bananas.
g(banana) = banana^2 - 5banana + 2. absurb analogy i know.

anyway now the qn says x=5,
g(x)=x^2-5x+2
replace all the x with 5,
g(5)=5^2-5(5)+2
which will works out to be
g(5) = 25-25+2= 2

2007-06-08 07:16:25 · answer #1 · answered by blackbobbypin 2 · 0 0

5² - 25 + 2 = 2

2007-06-08 07:17:17 · answer #2 · answered by Como 7 · 0 0

Substitute for x in that expression.

5^2 - 5 X 5 + 2 = 25 - 25 + 2 = 2

g(5) = 2

2007-06-08 07:04:40 · answer #3 · answered by Swamy 7 · 0 0

Just substitute x with the number 5 and solve normally (keep in mind order of operations).
g(5) = (5^2)-(5*5) +2
g(5) = 25-25+2
g(5) = 2
g(5)/5 = 2/5
g = 0.4

2007-06-08 07:08:00 · answer #4 · answered by spotsknight 3 · 1 1

g(x)=x^2-5x+2

So g(5) = 5^2-5*5+2
= 2

2007-06-08 07:04:51 · answer #5 · answered by Wal C 6 · 0 0

fedest.com, questions and answers